The Effect of Health Education on Complementary Feeding Practices in Children Aged 6–12 Months - Ditha Meirany Putri; Susianti; suharmanto; Dyah Wulan Sumekar Rengganis Wardani; Reni Zuraida (Jurnal Ilmiah STIKES Yarsi Mataram, 2026)
Appropriate complementary feeding (MP-ASI) is an important factor in supporting the growth and development of children aged 6–12 months. This study aimed to analyze the effect of health education on complementary feeding practices among mothers with children aged 6–12 months in the working area of UPT Puskesmas Kampung Sawah. A quasi-experimental pre-test and post-test control group design was employed involving 76 mothers, who were assigned to either an intervention group or a control group. The intervention consisted of health education delivered through lectures, group discussions, question-and-answer sessions, and educational materials on appropriate complementary feeding practices, conducted in two 60-minute sessions. Data were collected using a structured questionnaire and analyzed using the McNemar test and Mantel–Haenszel test. The results showed that health education significantly improved complementary feeding practices in the intervention group. Health education also increased the likelihood of improvement in complementary feeding behavior, with Odds Ratios ranging from 6.00 to 7.00, and these changes were not influenced by maternal education, age, or occupation. The study concluded that health education is an effective health promotion strategy for improving complementary feeding practices among mothers of children aged 6–12 months in primary healthcare settings.